Green Supply Chain Practices and Sustainable Performance: Moderating Role of Total Quality Management Practices in Electronic Industry of Thailand - Kittisak Jermsittiparsert; Puttisat Namdej; Sudawan Somjai (International Journal of Supply Chain Management, 2019)
This study examines and empirically investigates the green supply chain practices and sustainable performance. The study examines the impact of green supply chain practices on sustainability of performance of electronic industry of Thailand. Green supply chain management impact on environmental, economic and intangible performance of firms. Organizations follow GSCM practices as business strategy to achieve their long-term goals to enhance performance. Data was collected from firms of electronic industry of Thailand with GSCM activities and determine their performance. Data was collected through questionnaire to analyze the relationship between constructs of the study; GSCM entails Green Purchasing, Green Logistics, and Legislation for green environment and sustainable performance. Total quality management practices plays vital role in determine the performance, present study investigated moderating role of TQM practices between GSCM practices and sustainable performance at electronic industry of Thailand.